Effects of Dexamethasone‐21‐Isonicotinate on Peripheral Insulin Action in Dairy Cows 5 days after Surgical Correction of Abomasal Displacement. (29th November 2012) - Kusenda, M.; Kaske, M.; Piechotta, M.; Locher, L.; Starke, A.; Huber, K.; Rehage, J.
<x xml:space="preserve">Abstract</x> Background Dexamethasone frequently is used for treatment of ketosis in dairy cows, but its effects are not fully understood. Hypothesis Dexamethasone treatment affects whole body insulin sensitivity. Animals Twelve German Holstein cows, 2–4 weeks postpartum, 5 days after omentopexy to correct left abomasal displacement. Methods Randomized, blinded, case‐control study. Treatment with dexamethasone‐21‐isonicotinate (DG; 40 μg/kg IM; n = 6) or saline (control group [CG], 15 mL IM, n = 6) on day 0 (d0). Blood samples were obtained before (d0) and after treatment (d1 and d2), and analyzed for glucose, insulin, and nonesterified fatty acid (NEFA) concentrations. Hepatic triglycerides (TAG) were measured in liver samples taken on d0 and d2. Five consecutive hyperinsulinemic‐euglycemic clamps (HEC‐I‐V; insulin dosages: 0.1, 0.5, 2, 5, 10 mU/kg/min, respectively) were performed on d1 and steady state glucose infusion rate (SSGIR), insulin concentration (SSIC), insulin sensitivity index (ISI = SSGIR/SSIC), and plasma NEFA concentration (SSNEFA) were assessed. Results Compared with CG‐cows, DG‐cows on d1 had higher plasma glucose (P = .004) and insulin (P < .001) concentrations, decreased SSGIR (HEC‐II, P = .002; HEC‐IV, P = .033), ISI (HEC‐I, P < .015; HEC‐II, P = .004), and insulin‐stimulated decrease in SSNEFA (HEC‐II, P = .006; HEC‐III, P = .01; HEC‐IV, P = .003; HEC‐V, P = .011). Decrease in hepatic TAG content in DG‐cows was higher compared with CG‐cows (P < .001). Conclusions and Clinical Importance Dexamethasone decreases whole body insulin sensitivity and affects glucose and lipid metabolism in early lactating dairy cows.